The Influence of Credit Risk Management on the Profitability of Banks Listed on the Indonesian Stock Exchange - Nathanael, Felix; Evoney, Graficka; Zayyan, Aurum; Lestari, Henny (Jurnal Ilmiah Manajemen Kesatuan, 2023)
In general, every company strives to make as much profit as possible from its business activities. Financial performance is a measure of the company's success so that goals can be achieved as expected by the company. The purpose of this study is to see how the capital adequacy ratio (CAR), non-performing loans (NPL), loan loss provision (LLP), loan to deposit ratio (LDR) have an impact on bank profitability, in this study the profitability ratio used is return on assets (ROA). Conventional commercial bank companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022 are the samples used in this study. The data were tested using panel data regression analysis techniques. The results showed that (1) CAR has a positive impact on ROA, (2) NPL has a negative impact on ROA, (3) LLPR has no impact on ROA, and (4) LDR has no impact on ROA.